2010
DOI: 10.4049/jimmunol.1000676
|View full text |Cite
|
Sign up to set email alerts
|

Chemoattractant Receptors and Lymphocyte Egress from Extralymphoid Tissue: Changing Requirements during the Course of Inflammation

Abstract: Memory/effector T cells traffic efficiently through extralymphoid tissues, entering from the blood and leaving via the afferent lymph. During inflammation, T cell traffic into the affected tissue dramatically increases; however, the dynamics and mechanisms of T cell exit from inflamed tissues are poorly characterized. Here we show, using both a mouse and a sheep model, that large numbers of lymphocytes leave the chronically inflamed skin. Many T cells capable of producing IFN-γ and IL-17 also entered the drain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
121
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(138 citation statements)
references
References 59 publications
13
121
1
Order By: Relevance
“…The fact that transferred neutrophils cannot access poLNs in the absence of an inflammatory state matches our previous observations in which neutrophil influx was absent in nonimmunized mice (12). This is well in line with the fact that neutrophils are largely excluded from LNs in steady-state conditions, and that chronic inflammation induced by vigorous immunization causes LN hypertrophy and enhancement of leukocyte trafficking (30). It was demonstrated that CFA immunization provokes the expansion of the lymphatic network within and around LNs, and that during LN activation, HEVs undergo a process of growth and remodeling, thus permitting increased cell mobilization from blood and from the tissue that drains to those LNs (31, 32).…”
Section: Discussionsupporting
confidence: 90%
“…The fact that transferred neutrophils cannot access poLNs in the absence of an inflammatory state matches our previous observations in which neutrophil influx was absent in nonimmunized mice (12). This is well in line with the fact that neutrophils are largely excluded from LNs in steady-state conditions, and that chronic inflammation induced by vigorous immunization causes LN hypertrophy and enhancement of leukocyte trafficking (30). It was demonstrated that CFA immunization provokes the expansion of the lymphatic network within and around LNs, and that during LN activation, HEVs undergo a process of growth and remodeling, thus permitting increased cell mobilization from blood and from the tissue that drains to those LNs (31, 32).…”
Section: Discussionsupporting
confidence: 90%
“…These data suggest that lymphocyte trafficking through LVs in TLOs in NOD mice occurs under the control of the lymph S1P gradient and re-expression of its receptor by T cells, as occurs in LNs. These data are also consistent with the observation that FTY720 also prevents egress from inflamed tissues into afferent lymphatics (55,56) and raise the exciting possibility that inhibitors of LV function could prevent diabetes and other autoimmune diseases systemically by preventing trafficking from the TLO to the LNs. It is not known whether the LVs in TLOs produce S1P as they do in the rest of the body (4).…”
Section: Functions Of Lvs In Tlossupporting
confidence: 87%
“…It is possible that high CD62L expression is involved in the CCR7-independent tissue egress (29) and migratory behavior (30,31) of gd T cells, likely in conjunction with other, yet undefined, chemokine receptors. Tissue egress of Th1 cells involving alternative exit receptors has been described in mice with chronic skin inflammation recently (32).…”
Section: Discussionmentioning
confidence: 99%